ANALISA HASIL BIOGAS MENGGUNAKAN ISI RUMEN SAPI SEBAGAI STARTER - Renilaili, Renilaili (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2019)
Biogas is an environmentally friendly energy. The purpose of this experiment is to find out whether it is correct, by using a cumen rumen filler starter, the fermented biogas volume will become larger (more), compared to fermented cows fesses with water but not adding starter fluid of cow rumen contents. In this experiment 4 experiments were performed with the comparison (cows fesses: water: cow rumen fluid) are (1: 2: 0), (1: 2: 1), (1: 2: 2), and (1: 2 : 3). The experiment lasts for 40 days, but within 10 days it has already produced biogas, this biogas will continue and there is reaction of asidogenesis and methanogenic reaction. From the observations made, the amount of biogas volume is also influenced by raw material ratio and fermentation time (25,80 cm3) with raw material ratio (1: 2: 2) and fermentation time for 30 days. The result of this biogas is quite significant (59.3%,) more, here the starter function is quite dominant to increase the expected biogas production